2020
DOI: 10.3389/fonc.2020.00839
|View full text |Cite
|
Sign up to set email alerts
|

Triple Immunotherapy Overcomes Immune Evasion by Tumor in a Melanoma Mouse Model

Abstract: Background: Melanoma is a malignancy with increasing incidence that underlies most skin cancer-related deaths. Advanced melanoma patients still have poor prognosis despite recently developed immunotherapies. This study devises a triple immunotherapy to treat melanoma in a mouse model. The combination includes anti-cytotoxic T-lymphocyte-associated protein 4 (CTLA4) antibodies, Monophosphoryl-lipid-A (MPLA), and an Indolamine-Dioxygenase-1 (IDO1) inhibitor. The aim of the study is, first, to rule out any major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Similar to other tumor models (12,42,43), intratumoral (i.t) MPLA alone had no effect on MMTV-PyMT orthotopic breast tumor growth (Fig. 3A left, Fig.…”
Section: Coa Enhances Macrophage-dependent Tlr Agonist Anti-tumor Act...supporting
confidence: 75%
“…Similar to other tumor models (12,42,43), intratumoral (i.t) MPLA alone had no effect on MMTV-PyMT orthotopic breast tumor growth (Fig. 3A left, Fig.…”
Section: Coa Enhances Macrophage-dependent Tlr Agonist Anti-tumor Act...supporting
confidence: 75%
“…It decreases tryptophan(Trp) and produces a series of toxic kynurenine(Kyn) metabolites ( 43 ). The toxic Kyn metabolites directly suppress the effector T cell response by favoring differentiation of Tregs ( 44 , 45 ). The immune checkpoint is a key molecule in T-cell dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Jallad et al. found that the triple immune therapy was capable of significantly enhancing the natural killer cell counts as well as the CD3 + CD4 + /T reg and CD3 + CD8 + /Treg ratios possibly enhancing the anti-tumorigenic environment ( 44 ). The present study also provides support for the application of IDO1 inhibitors in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, anti-CTLA-4 therapy may enhance antitumor cytotoxicity of NK cells in both a direct and indirect manner such as depletion of CTLA-4 + Treg cells. Triple immunotherapy with anti-CTLA4 antibodies, monophosphoryl-lipid-A, and indolamine-dioxygenase-1 inhibitor has been reported to enhance NK cell counts and the CD3 + CD4 + /Treg and CD3 + CD8 + /Treg ratios, in addition to the reduction in tumor mass, in a murine melanoma model ( 44 ). Combination therapies could provide additional benefits, although the B7/CTLA-4 axis may not play a key role in NK cell activation ( 45 , 46 ).…”
Section: Immune Checkpoint Receptorsmentioning
confidence: 99%